A preparation process of PEEK composite insulated electromagnetic wire
Through the mixed composite composite and three-layer insulation structure design of nano-silica hyperbranched polyester and PEEK, the problem of insufficient insulation performance of PEEK insulating materials in high voltage and high temperature environments is solved, and significant insulation performance and high temperature resistance are achieved. .
Patent Information
- Application Number
- CN202411136354.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-19
AI Technical Summary
The existing PEEK insulating materials lack insulation performance and reliability in high voltage and high temperature environments, and the interface problems of the composite insulating structures lead to a decrease in insulation effect.
The nano-silica hyperbranched polyester and PEEK are used to mix and combine nano-silica hyperbranched polyester to design a three-layer insulating structure. Through the unique structure of nano-silica hyperbranched polyester and the excellent performance of PEEK, the synergistic improvement of materials and processes is achieved.
It significantly improves the insulation performance and high temperature resistance of electromagnetic wires, realizes the use requirements under harsh working conditions such as high voltage and high frequency, and optimizes the interface compatibility between the insulating layers.
Smart Images

Figure CN118737584B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wires, in particular to a preparation process of a PEEK composite insulated electromagnetic wire. Background Art
[0002] Polyetheretherketone (PEEK) is an excellent thermoplastic engineering plastic with high heat resistance, excellent mechanical properties and easy processing characteristics. It has broad application prospects in the field of electromagnetic wire insulation. However, the insulation performance and reliability of a single PEEK insulation layer under harsh environments such as high voltage and high temperature still need to be improved.
[0003] At present, composite insulation structures usually include an intermediate layer and an outer insulation layer, but simply combining different materials to form an insulation layer is prone to forming an interface between the layers, resulting in a decrease in insulation effect. In addition, existing insulation materials are also insufficient in high temperature resistance and are prone to thermal decomposition and insulation failure in long-term high temperature environments.
[0004] Therefore, it is urgent to develop a new composite insulation material system that can ensure excellent insulation performance while taking into account high heat resistance and good interface compatibility through reasonable material selection and structural design to meet the increasingly stringent requirements for electromagnetic wire insulation. In view of the above technical problems, the present invention proposes a nano-silicon dioxide hyperbranched polyester / PEEK composite multilayer insulation structure, which aims to comprehensively improve the insulation performance and reliability of electromagnetic wires from the perspective of materials and processes. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a preparation process of a PEEK composite insulated electromagnetic wire, which has excellent insulation and high temperature resistance properties.
[0007] (II) Technical solution
[0008] To achieve the above object, the present invention provides the following technical solution: a preparation process of a PEEK composite insulated electromagnetic wire, comprising the following steps:
[0009] (1) adding polylactic acid to tetrahydrofuran solvent to dissolve it, adding succinic anhydride after dissolution, stirring and slowly dropping stannous octoate catalyst, reacting in a water bath at 70-110° C. for 3-6 hours, and after the reaction, removing the solvent by reduced pressure distillation, washing the product, filtering and drying to obtain carboxyl polylactic acid;
[0010] (2) 80-100 parts by weight of acrylic acid, 10-15 parts by weight of vinyl triethoxysilane, 70-90 parts by weight of deionized water and 2-4 parts by weight of propylene glycol are mixed to form solution A, 3-6 parts by weight of mercaptopropionic acid, 0.1-0.2 parts by weight of vitamin C, 40-60 parts by weight of deionized water and 2-5 parts by weight of propylene glycol are mixed to form solution B, solution B is added dropwise to solution A which is continuously stirred, and the reaction is continued at 60-90° C. with stirring for 4-8 hours to obtain an acrylic modified silane coupling agent;
[0011] (3) adding CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding carboxyl polylactic acid, acrylic acid-modified silane coupling agent and dibutyltin dilaurate to carry out esterification reaction at 80-120° C. for 20-24 hours, washing with acetone for 3-6 hours after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0012] (4) adding the hyperbranched polyester into a dichloromethane solvent, then adding nano-silica, stirring and reacting at 40-70° C. for 4-6 hours to obtain nano-silica hyperbranched polyester;
[0013] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and then the mixture is baked and cooled to obtain a first insulating layer; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester again, and then the mixture is dried to obtain a second insulating layer; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and then the mixture is dried to obtain a third insulating layer; then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0014] Preferably, the mass ratio of polylactic acid, succinic anhydride and stannous octoate catalyst in (1) is 1.5-2.1:1:0.01-0.03.
[0015] Preferably, the mass ratio of solution A to solution B in (2) is 40-50:22-34.
[0016] Preferably, the mass ratio of CBz-based 2-amino-1,3-propanediol, carboxyl polylactic acid, acrylic acid-modified silane coupling agent, and dibutyltin dilaurate in (3) is 2.1-3.4:1:1.5-1.8:0.03-0.05.
[0017] Preferably, the mass ratio of the hyperbranched polyester to the nano-silicon dioxide in (4) is 1.1-1.6:1.
[0018] Preferably, in (5), the thickness of the first insulating layer is 10-20 μm; the thickness of the second insulating layer is 15-30 μm; and the thickness of the third insulating layer is 50-80 μm.
[0019] Preferably, the mass ratio of the mixed solution of nano-silica hyperbranched polyester and polyetheretherketone paint in (5) is 2.1-2.6:1.
[0020] The present invention has the following beneficial technical effects:
[0021] Significantly improve the electrical insulation performance of the electromagnetic wire: The present invention mixes nano-silica hyperbranched polyester with PEEK and designs a three-layer insulation structure to give full play to the synergistic effect of the two materials. The inorganic nanoparticles in the nano-silica hyperbranched polyester have excellent electrical insulation, while the hyperbranched polyester and PEEK provide good flexibility and mechanical strength. The combination of the three significantly improves the insulation performance of the electromagnetic wire and can meet the use requirements under harsh working conditions such as high voltage and high frequency.
[0022] Greatly improve the high temperature resistance of the magnet wire: Hyperbranched polyester and PEEK are both high temperature resistant polymer materials, and the insulation layer prepared by the composite can maintain excellent thermal stability and mechanical properties at high temperatures. At the same time, the addition of nano-silicon dioxide particles further improves the heat resistance of the material. Compared with a single insulating material, the temperature resistance of the composite insulated magnet wire of the present invention is significantly improved, which can meet the application requirements in high temperature environments.
[0023] Achieving high interfacial compatibility between insulating layers: The present invention adopts a three-layer insulating structure in which the inner and outer layers are nano-silicon dioxide hyperbranched polyester / PEEK mixed layers, and the middle layer is a nano-silicon dioxide hyperbranched polyester layer. This gradient design helps to alleviate the material difference between the inner and outer layers and improve the interfacial compatibility. The unique three-dimensional spherical structure and a large number of terminal groups of hyperbranched polyester can form more intermolecular forces and chain entanglements with PEEK, thereby enhancing interfacial bonding. The introduction of nano-silicon dioxide also improves interfacial compatibility. A close molecular connection network is formed between the three insulating layers, effectively eliminating the interface problems of conventional composite insulating layers.
[0024] Optimize the comprehensive performance of electromagnetic wire: The composite insulation material system of the present invention not only has excellent electrical insulation and heat resistance, but also has good mechanical properties and chemical stability. Nano-silica hyperbranched polyester has both the high strength of inorganic nanoparticles and the toughness of hyperbranched polymers, complementing PEEK to improve the mechanical strength, impact resistance and wear resistance of the electromagnetic wire. At the same time, both hyperbranched polyester and PEEK have excellent chemical resistance, which can prevent the electromagnetic wire from being corroded and degraded in harsh environments.
[0025] The process is simple and easy to promote and apply in industry: The present invention adopts a multi-layer composite insulation preparation process of coating-baking-cooling, which is simple to operate and suitable for large-scale industrial production. The raw materials are all commercially available products or obtained by simple synthesis, and the cost is low. By adjusting the process parameters such as the thickness of the insulation layer and the number of coatings, composite insulated electromagnetic wire products that meet different application requirements can be flexibly prepared, and have broad market application prospects. DETAILED DESCRIPTION
[0026] Reference journal "Synthesis", 2002, No.15, ISSN0039-7881, Preparation of CBz-based 2-amino-1,3-propanediol: 0.5 g of 2-amino-1,3-propanediol and 2.3 g of benzylphenyl carbonate are reacted at 25°C for 12 hours to obtain CBz-based 2-amino-1,3-propanediol.
[0027] Embodiment 1:
[0028] (1) Add 4.2 g of polylactic acid to tetrahydrofuran solvent to dissolve it, add 2 g of succinic anhydride after dissolution, stir and slowly drop 0.02 g of stannous octoate catalyst, react in a water bath at 70° C. for 3 h, remove the solvent by vacuum distillation after the reaction, wash the product, filter and dry to obtain carboxyl polylactic acid;
[0029] (2) 8 g of acrylic acid, 1 g of vinyl triethoxysilane, 7 g of deionized water and 0.2 g of propylene glycol were mixed to prepare solution A, 0.3 g of mercaptopropionic acid, 0.01 g of vitamin C, 4 g of deionized water and 0.2 g of propylene glycol were mixed to prepare solution B, solution B was added dropwise to solution A which was continuously stirred, wherein the mass ratio of solution A to solution B was 40:22, and the stirring reaction was continued at 60°C for 4 h to obtain an acrylic modified silane coupling agent;
[0030] (3) adding 2.1 g of CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding 1 g of carboxyl polylactic acid, 1.5 g of acrylic acid-modified silane coupling agent and 0.03 g of dibutyltin dilaurate for esterification reaction at 80° C. for 20 h, washing with acetone for 3 h after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0031] (4) adding 2.2 g of hyperbranched polyester into a dichloromethane solvent, and then adding 2 g of nano-silica, stirring and reacting at 40° C. for 4 h to obtain nano-silica hyperbranched polyester;
[0032] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 10 μm; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 15 μm; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 50 μm; wherein the mass ratio of the mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is 2.1:1, and then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0033] Embodiment 2:
[0034] (1) Add 6 g of polylactic acid to tetrahydrofuran solvent to dissolve it, add 4 g of succinic anhydride after dissolution, stir and slowly drop 0.12 g of stannous octoate catalyst, react in a water bath at 110° C. for 6 h, remove the solvent by reduced pressure distillation after the reaction, wash the product, filter and dry to obtain carboxyl polylactic acid;
[0035] (2) 10 g of acrylic acid, 1.5 g of vinyl triethoxysilane, 9 g of deionized water and 0.4 g of propylene glycol were mixed to prepare solution A, 0.6 g of mercaptopropionic acid, 0.02 g of vitamin C, 6 g of deionized water and 0.5 g of propylene glycol were mixed to prepare solution B, solution B was added dropwise to solution A which was continuously stirred, wherein the mass ratio of solution A to solution B was 50:34, and the stirring reaction was continued at 90°C for 8 h to obtain an acrylic modified silane coupling agent;
[0036] (3) adding 6.8 g of CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding 2 g of carboxyl polylactic acid, 3.6 g of acrylic acid-modified silane coupling agent and 0.1 g of dibutyltin dilaurate for esterification reaction at 120° C. for 24 h, washing with acetone for 6 h after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0037] (4) adding 4.8 g of hyperbranched polyester into dichloromethane solvent, and then adding 3 g of nano-silica, stirring and reacting at 70° C. for 6 h to obtain nano-silica hyperbranched polyester;
[0038] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 20 μm; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 30 μm; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 80 μm; wherein the mass ratio of the mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is 2.6:1, and then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0039] Embodiment 3:
[0040] (1) Add 5.1 g of polylactic acid to tetrahydrofuran solvent to dissolve it, add 3 g of succinic anhydride after dissolution, stir and slowly drop 0.07 g of stannous octoate catalyst, react in a water bath at 90° C. for 4.5 h, remove the solvent by reduced pressure distillation after the reaction, wash the product, filter and dry to obtain carboxyl polylactic acid;
[0041] (2) 9 g of acrylic acid, 1.25 g of vinyl triethoxysilane, 8 g of deionized water and 0.3 g of propylene glycol were mixed to prepare solution A, 0.45 g of mercaptopropionic acid, 0.015 g of vitamin C, 5 g of deionized water and 0.35 g of propylene glycol were mixed to prepare solution B, solution B was added dropwise to solution A which was continuously stirred, wherein the mass ratio of solution A to solution B was 45:28, and the reaction was continued at 75°C with stirring for 6 h to obtain an acrylic modified silane coupling agent;
[0042] (3) adding 4.45 g of CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding 1.5 g of carboxyl polylactic acid, 2.55 g of acrylic acid-modified silane coupling agent and 0.065 g of dibutyltin dilaurate for esterification reaction at 100° C. for 22 h, washing with acetone for 4.5 h after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0043] (4) adding 3.5 g of hyperbranched polyester into dichloromethane solvent, and then adding 2.5 g of nano-silica, stirring and reacting at 55° C. for 5 h to obtain nano-silica hyperbranched polyester;
[0044] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 15 μm; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 22.5 μm; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 65 μm; wherein the mass ratio of the mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is 2.35:1, and then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0045] Embodiment 4:
[0046] (1) Add 4.2 g of polylactic acid to tetrahydrofuran solvent to dissolve it, add 2 g of succinic anhydride after dissolution, stir and slowly drop 0.02 g of stannous octoate catalyst, react in a water bath at 70° C. for 3 h, remove the solvent by vacuum distillation after the reaction, wash the product, filter and dry to obtain carboxyl polylactic acid;
[0047] (2) 8 g of acrylic acid, 1 g of vinyl triethoxysilane, 7 g of deionized water and 0.2 g of propylene glycol were mixed to prepare solution A, 0.3 g of mercaptopropionic acid, 0.01 g of vitamin C, 4 g of deionized water and 0.2 g of propylene glycol were mixed to prepare solution B, solution B was added dropwise to solution A which was continuously stirred, wherein the mass ratio of solution A to solution B was 40:22, and the stirring reaction was continued at 60°C for 4 h to obtain an acrylic modified silane coupling agent;
[0048] (3) adding 6.8 g of CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding 2 g of carboxyl polylactic acid, 3.6 g of acrylic acid-modified silane coupling agent and 0.1 g of dibutyltin dilaurate for esterification reaction at 120° C. for 24 h, washing with acetone for 6 h after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0049] (4) adding 4.8 g of hyperbranched polyester into dichloromethane solvent, and then adding 3 g of nano-silica, stirring and reacting at 70° C. for 6 h to obtain nano-silica hyperbranched polyester;
[0050] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 15 μm; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 22.5 μm; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 65 μm; wherein the mass ratio of the mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is 2.35:1, and then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0051] Embodiment 5:
[0052] (1) Add 6 g of polylactic acid to tetrahydrofuran solvent to dissolve it, add 4 g of succinic anhydride after dissolution, stir and slowly drop 0.12 g of stannous octoate catalyst, react in a water bath at 110° C. for 6 h, remove the solvent by reduced pressure distillation after the reaction, wash the product, filter and dry to obtain carboxyl polylactic acid;
[0053] (2) 10 g of acrylic acid, 1.5 g of vinyl triethoxysilane, 9 g of deionized water and 0.4 g of propylene glycol were mixed to prepare solution A, 0.6 g of mercaptopropionic acid, 0.02 g of vitamin C, 6 g of deionized water and 0.5 g of propylene glycol were mixed to prepare solution B, solution B was added dropwise to solution A which was continuously stirred, wherein the mass ratio of solution A to solution B was 50:34, and the stirring reaction was continued at 90°C for 8 h to obtain an acrylic modified silane coupling agent;
[0054] (3) adding 4.45 g of CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding 1.5 g of carboxyl polylactic acid, 2.55 g of acrylic acid-modified silane coupling agent and 0.065 g of dibutyltin dilaurate for esterification reaction at 100° C. for 22 h, washing with acetone for 4.5 h after the reaction, filtering and drying to obtain a hyperbranched polyester;
[0055] (4) adding 3.5 g of hyperbranched polyester into dichloromethane solvent, and then adding 2.5 g of nano-silica, stirring and reacting at 55° C. for 5 h to obtain nano-silica hyperbranched polyester;
[0056] (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 10 μm; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 15 μm; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 50 μm; wherein the mass ratio of the mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is 2.1:1, and then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0057] Comparative Example 1:
[0058] The conductor is subjected to wire drawing and forming treatment, and then polyetheretherketone paint is coated on the surface thereof, and then the conductor is baked and cooled to obtain a PEEK composite insulated electromagnetic wire.
[0059] Comparative Example 2:
[0060] The conductor is subjected to a wire drawing process, and then the surface of the conductor is coated with nano-silicon dioxide hyperbranched polyester, and then the conductor is baked and cooled to obtain a first insulating layer with a thickness of 10 μm; then the surface of the first insulating layer is coated with nano-silicon dioxide hyperbranched polyester, and then the conductor is dried to obtain a second insulating layer with a thickness of 15 μm; finally, the surface of the second insulating layer is coated with nano-silicon dioxide hyperbranched polyester, and then the conductor is dried to obtain a third insulating layer with a thickness of 50 μm; then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0061] Comparative Example 3:
[0062] The conductor is subjected to a wire drawing process, and then a mixed liquid of polyetheretherketone paint is coated on the surface thereof, and the mixture is baked and cooled to obtain a first insulating layer with a thickness of 10 μm; then the surface of the first insulating layer is coated with nano-silicon dioxide hyperbranched polyester, and the mixture is dried to obtain a second insulating layer with a thickness of 15 μm; finally, the surface of the second insulating layer is coated with a mixed liquid of polyetheretherketone paint, and the mixture is dried to obtain a third insulating layer with a thickness of 50 μm; then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
[0063] The electromagnetic wires prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were cut into samples with a length of 100 mm. A breakdown voltage tester was used to increase the voltage at a rate of 100 V / s until the sample broke down, and the voltage value at the time of breakdown was recorded. Three parallel samples were prepared for each example and comparative example, and the test results were averaged. The specific test results are shown in Table 1. .
[0064] Table 1 Breakdown voltage test of PEEK composite insulated magnet wire.
[0065] .
[0066] The breakdown voltages of the PEEK composite insulated electromagnetic wires of Examples 1-5 are all greater than or equal to 13KV, while the breakdown voltages of Comparative Examples 1-3 are significantly lower, being only 0.2KV, 1.2KV, and 1.5KV, respectively. The above experimental results illustrate that:
[0067] The nano-silicon dioxide hyperbranched polyester and polyetheretherketone paint used in Examples 1-5 were mixed as the insulating layer, which significantly improved the withstand voltage strength and insulation performance of the insulated magnet wire. The breakdown voltage reached a high level of more than 13KV, which is 8-65 times that of the comparative example, indicating that this composite insulating material can withstand higher voltages and has excellent insulation capabilities.
[0068] Comparative Example 1 uses only a single PEEK as insulation, and the breakdown voltage is the lowest, only 0.2KV, indicating that the insulation performance of a single PEEK is poor and insufficient to meet the high withstand voltage requirements. Comparative Example 2 uses pure nano-silicon dioxide hyperbranched polyester as insulation, and the breakdown voltage is improved to 1.2KV, but it is still far lower than the embodiment. This shows that it is difficult to achieve an ideal insulation effect by using only a single insulating material, whether it is PEEK or hyperbranched polyester.
[0069] Comparative Example 3 uses PEEK and nano-silicon dioxide hyperbranched polyester as different insulating layers, and the breakdown voltage is slightly higher than that of Comparative Example 2, which is 1.5KV, but it is still far from the level of the embodiment. This shows that simply combining the two materials as different layers cannot exert the best synergistic insulation effect. The coating combination provided by Examples 1-5 of the present invention has a very obvious synergistic insulation effect compared with the comparative example.
[0070] The thickness configuration of the insulating layer of Examples 1-5 is also slightly different from that of the comparative example. Although the thicknesses of the examples are different, their breakdown voltages all reach a high level of more than 13KV, indicating that within a certain thickness range, the insulation performance mainly depends on the properties of the material. Although the thickness of the insulating layer of Comparative Examples 2 and 3 is the same as that of Examples 1 and 5, the breakdown voltage is one order of magnitude lower, further confirming the unique superiority of the composite materials used in the examples.
[0071] In summary, it can be concluded that Examples 1-5 use nano-silicon dioxide hyperbranched polyester prepared by a specific process and mixed with PEEK as a composite insulating layer. By exerting the synergistic effect of the two materials, the withstand voltage level of the insulated electromagnetic wire is significantly improved, and the excellent insulation performance of more than 13KV is achieved. In contrast, the comparative example uses a single insulating material or a simple combination of different components, and it is difficult to obtain a satisfactory insulation effect, and the breakdown voltage is only a few tens of times that of the embodiment. This comparison result strongly proves the advancement of the composite insulating material and its preparation process of the present invention.
[0072] The PEEK composite insulated electromagnetic wires prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were subjected to a DC insulation resistance test. Using direct current and a resistance tester, a certain voltage was applied to the insulating material to be tested. The electromagnetic wires prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to an insulation test by removing the composite insulating material having an outer layer length of 3 cm, a width of 2 cm, and a height of 0.09 mm. Three parallel samples were prepared for each Example and Comparative Example, and the test results were averaged. The test results are shown in Table 2.
[0073] Table 2 DC insulation resistance test results.
[0074] .
[0075] It can be seen that the DC insulation resistance of the PEEK composite insulated magnet wires of Examples 1-5 is 2*10 16 Ω, while the insulation resistances of Comparative Examples 1-3 are 2*10 4 Ω、2*10 7 Ω and 2*10 10 Ω. This result shows that:
[0076] The nano-silicon dioxide hyperbranched polyester and PEEK mixed composite insulation material used in Examples 1-5 exhibited extremely high insulation resistance, reaching 2*10 16 This shows that the composite insulation material has excellent insulation performance, can greatly suppress leakage current and insulation loss, maintain long-term stable insulation performance under harsh working conditions such as high voltage and high current, and ensure safe and reliable operation of the system.
[0077] Comparative Example 1 uses a single PEEK material for insulation, and its insulation resistance is only 2*10 4 Ω, which is 12 orders of magnitude different from the example. This shows that the insulation performance of single PEEK is poor and it is difficult to meet the requirements of high insulation. Comparative Example 2 uses pure nano-silicon dioxide hyperbranched polyester as insulation, and the insulation resistance reaches 2*10 7Ω, although it is improved compared with PEEK, there is still a significant gap of 9 orders of magnitude compared with the embodiment. This shows that although hyperbranched polyester has certain insulation properties, it is still not enough to meet the performance requirements of ultra-high insulation when used alone.
[0078] Comparative Example 3: PEEK and hyperbranched polyester are used as different insulation layers, and the insulation resistance reaches 2*10 10 Ω, which is further improved compared with Comparative Example 2, but still 6 orders of magnitude lower than that of Example 2. This result suggests that simply combining PEEK and hyperbranched polyester cannot maximize the synergistic effect of the two materials, and the improvement of insulation performance is limited.
[0079] The reason why Examples 1-5 can obtain up to 2*10 16 The key to the ultra-high insulation resistance of Ω is the use of nano-silicon dioxide hyperbranched polyester prepared by a specific process and mixed with PEEK. Through this composite method, the high insulation properties of hyperbranched polyester are brought into play, while the excellent mechanical and thermal stability of PEEK are taken into account. At the same time, the introduction of nano-silicon dioxide further enhances the insulation strength. The synergistic effect between multiple components has improved the insulation performance by an order of magnitude, reaching a level that cannot be achieved by a single component.
[0080] Although the thickness ratios of the insulation layers in Examples 1-5 are slightly different, their insulation resistance test results are highly consistent, all reaching 2*10 16 This shows that within a certain thickness range, as long as a suitable composite insulating material is used, the insulation resistance mainly depends on the insulation properties of the material itself, rather than the thickness of the insulating layer. Although the thickness of the insulating layer of Comparative Examples 2 and 3 is comparable to that of Examples 1 and 5, the insulation resistance is 6-9 orders of magnitude lower, which further confirms the decisive role of material properties.
[0081] In summary, the nano-silicon dioxide hyperbranched polyester and PEEK mixed composite insulation material used in the embodiment of the present invention has a synergistic effect between the components, so that the DC insulation resistance of the PEEK composite insulated electromagnetic wire reaches 2*10 16 The ultra-high level of Ω is 6-12 orders of magnitude higher than the control ratio, which fully demonstrates the excellent insulation performance of the composite material. This result is mutually confirmed with the previous breakdown voltage experiment, and together shows that the composite insulation material of the present invention has significant advantages in multiple performance indicators such as high withstand voltage and high insulation, and provides a new material solution for the design and application of high-performance special electromagnetic wires, which is of great value for improving the safety and reliability of electrical equipment and reducing energy consumption.
[0082] The PEEK composite insulated electromagnetic wires prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were subjected to a thermal performance test by a thermogravimetric analyzer, with a nitrogen atmosphere, a heating rate of 20°C / min, and a maximum temperature of 800°C. The outer layer of the electromagnetic wires of Examples 1-5 and Comparative Examples 1-3 was 15 g in weight, and 3 parallel samples were prepared for each Example and Comparative Example. The test results were averaged. The test results are shown in Table 3.
[0083] Table 3 High temperature resistance test results.
[0084] .
[0085] According to the mass residual rate data at 800 degrees Celsius provided in Table 3, the mass residual rates of the PEEK composite insulated electromagnetic wires of Examples 1-5 at a high temperature of 800 degrees Celsius are all above 88.7%, among which Examples 1, 2, and 5 reach above 91.6%. The mass residual rates of Comparative Examples 1-3 are significantly lower, only 42.3%, 64.2%, and 65.4%, respectively. This experimental result further illustrates the following issues from the perspective of the high temperature resistance of the material:
[0086] The nano-silica hyperbranched polyester and PEEK mixed composite insulation materials used in Examples 1-5 not only have excellent electrical insulation properties (as shown in the previous breakdown voltage and insulation resistance experiments), but also show excellent high temperature resistance. Under high temperature conditions of 800 degrees Celsius, the mass residual rate of the embodiment is still maintained at a high level of 88.7-91.7%, which means that most of the materials can withstand high temperatures without decomposition or carbonization, maintaining good structural integrity. The excellent high temperature resistance ensures the long-term use reliability of the PEEK composite insulated electromagnetic wire in high temperature environments and broadens its application range.
[0087] Comparative Example 1 uses a single PEEK material for insulation, and the mass residual rate at 800 degrees Celsius is only 42.3%, indicating that the single PEEK undergoes serious thermal decomposition at high temperatures, the insulation structure is damaged, and it is difficult to maintain good insulation performance. This once again confirms the shortcomings of the single PEEK material in terms of insulation performance. Comparative Examples 2 and 3 respectively use pure nano-silica hyperbranched polyester and a simple combination of PEEK / hyperbranched polyester. Although the mass residual rate at 800 degrees Celsius is improved compared to that of single PEEK, reaching 64.2% and 65.4%, it is still 20-25 percentage points lower than that of the embodiment. It can be seen that the high temperature resistance of a single hyperbranched polyester or a simple material combination is limited.
[0088] The key reason why Examples 1-5 can achieve such excellent high-temperature mass residual rate is the use of deep mixed composites of nano-silicon dioxide hyperbranched polyester and PEEK. By optimizing the preparation process and utilizing the high-temperature stability and barrier properties of nano-silicon dioxide, the heat resistance of the hyperbranched polyester matrix is improved; at the same time, the introduction of hyperbranched polyester also improves the thermal stability of the PEEK molecular chain. The two components form a synergistic complement in the composite material, thereby greatly improving the high-temperature resistance of the entire insulation system, far exceeding the single-component material.
[0089] The mass residual rate at 800 degrees Celsius of Examples 1, 2, and 5 reached more than 91.6%, slightly higher than 88.7% of Examples 3 and 4. This shows that the formula composition and preparation process of the first three examples are more conducive to exerting the heat-resistant synergistic effect of nano-silica hyperbranched polyester and PEEK, and can be used as a preferred solution. But in general, the mass residual rate of the five examples is at a high level of more than 88%, and the high temperature resistance performance is outstanding.
[0090] Comparing the experimental results with the aforementioned breakdown voltage and insulation resistance experiments, it can be seen that Examples 1-5 not only perform well in electrical insulation performance, but also have excellent high temperature resistance, and multiple performance indicators are synergistically improved. This fully demonstrates the comprehensive performance advantages of nano-silicon dioxide hyperbranched polyester / PEEK composite insulation materials, and is an all-round optimized insulation solution. In contrast, the comparative examples are difficult to meet high performance requirements in various indicators such as electrical insulation and heat resistance.
[0091] In summary, the experimental results of the high-temperature mass residual rate at 800 degrees Celsius show that the nano-silica hyperbranched polyester / PEEK composite insulation material used in the embodiment of the present invention not only has excellent electrical insulation properties, but also exhibits excellent high temperature resistance. It can still maintain a high quality residual rate of 88.7-91.7% at 800 degrees Celsius, far exceeding the level of a single material or a simple combination. The high heat resistance of the embodiment material is derived from the good synergy and complementarity between the components, which together build a high-temperature resistant insulation protection system. The combination of excellent electrical insulation and heat resistance enables the PEEK composite insulated electromagnetic wire to operate stably and reliably under harsh environments such as high temperature and high pressure, greatly broadening its scope of application and providing a cost-effective material selection for the field of special electromagnetic wires.
[0092] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for preparing a PEEK composite insulated electromagnetic wire, characterized in that: The preparation process comprises the following steps: (1) adding polylactic acid to tetrahydrofuran solvent to dissolve it, adding succinic anhydride after dissolution, stirring and slowly dropping stannous octoate catalyst, reacting in a water bath at 70-110° C. for 3-6 hours, and after the reaction, removing the solvent by reduced pressure distillation, washing the product, filtering and drying to obtain carboxyl polylactic acid; (2) 80-100 parts by weight of acrylic acid, 10-15 parts by weight of vinyl triethoxysilane, 70-90 parts by weight of deionized water and 2-4 parts by weight of propylene glycol are mixed to form solution A, 3-6 parts by weight of mercaptopropionic acid, 0.1-0.2 parts by weight of vitamin C, 40-60 parts by weight of deionized water and 2-5 parts by weight of propylene glycol are mixed to form solution B, solution B is added dropwise to solution A which is continuously stirred, and the reaction is continued at 60-90° C. with stirring for 4-8 hours to obtain an acrylic modified silane coupling agent; (3) adding CBz-based 2-amino-1,3-propanediol to N,N-dimethylformamide solvent for dissolution, and then adding carboxyl polylactic acid, acrylic acid-modified silane coupling agent and dibutyltin dilaurate to carry out esterification reaction at 80-120° C. for 20-24 hours, washing with acetone for 3-6 hours after the reaction, filtering and drying to obtain a hyperbranched polyester; (4) adding the hyperbranched polyester into a dichloromethane solvent, then adding nano-silica, stirring and reacting at 40-70° C. for 4-6 hours to obtain nano-silica hyperbranched polyester; (5) The conductor is subjected to a wire drawing process, and then a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint is coated on its surface, and then the mixture is baked and cooled to obtain a first insulating layer; then the surface of the first insulating layer is coated with nano-silica hyperbranched polyester again, and then the mixture is dried to obtain a second insulating layer; finally, the surface of the second insulating layer is coated with a mixture of nano-silica hyperbranched polyester and polyetheretherketone paint, and then the mixture is dried to obtain a third insulating layer; then the conductor is rolled and packaged to obtain a PEEK composite insulated electromagnetic wire.
2. The process for preparing the PEEK composite insulated magnet wire according to claim 1, characterized in that: The mass ratio of polylactic acid, succinic anhydride and stannous octoate catalyst in (1) is 1.5-2.1:1:0.01-0.
03.
3. The preparation process of the PEEK composite insulated magnet wire according to claim 1, characterized in that: The mass ratio of solution A to solution B in (2) is 40-50:22-34.
4. The process for preparing the PEEK composite insulated magnet wire according to claim 1, characterized in that: The mass ratio of CBz-based 2-amino-1,3-propanediol, carboxyl polylactic acid, acrylic acid-modified silane coupling agent, and dibutyltin dilaurate in (3) is 2.1-3.4:1:1.5-1.8:0.03-0.
05.
5. The process for preparing the PEEK composite insulated magnet wire according to claim 1, characterized in that: The mass ratio of the hyperbranched polyester to the nano-silicon dioxide in (4) is 1.1-1.6:
1.
6. The process for preparing the PEEK composite insulated magnet wire according to claim 1, characterized in that: In the (5), the thickness of the first insulating layer is 10-20 μm; the thickness of the second insulating layer is 15-30 μm; and the thickness of the third insulating layer is 50-80 μm.
7. The process for preparing the PEEK composite insulated magnet wire according to claim 1, characterized in that: The mass ratio of the mixed liquid of the first insulating layer and the third insulating layer of nano-silica hyperbranched polyester and polyetheretherketone paint in (5) is 2.1-2.6:1.
Citation Information
Patent Citations
Anti-aging enamel insulated wire
CN106519649A
Preparation method of enameled wire with high corona onset voltage
CN116665988A